The Potential of Telenomus remus Nixon (Hymenoptera: Scelinoidae) as Biocontrol Agent for the New Fall Armyworm S. frugiperda (Lepidoptera: Noctuidae) in Indonesia - Sari, Adha; Buchori, Damayanti; Nurkomar, Ihsan (Universitas Muhammadiyah Yogyakarta, 2020)
The fall armyworm Spodoptera frugiperda is an emerging new pest species in several Asian countries including Indonesia. This pest can be a threat to Indonesian agriculture because this pest has been reported to cause many losses in other countries. As a preemptive and ecofriendly control strategy, a research to study the performance of Telenomus remus as potential biocontrol agent of this pest was done in laboratory scale. Research was done by exposing an adult female to 50 eggs of S. frugiperda in a cluster. We also exposed the female parasitoid to another 50 eggs of S. litura in a cluster for comparison since this parasitoid had been reported as S. litura egg parasitoid in Indonesia previously. Results showed that there are no difference in the numbers of parasitized eggs, parasitism rate, survival rates and percent females of T. remus reared from both S. frugiperda and S litura, which implies the effectiveness of T. remus as a candidate for bio control agent for S. frugiperda.